Warm-up practices in elite snowboard athletes - Sporer, B. C.; Cote, A.; Sleivert, G. (International Journal of Sports Physiology and Performance, 2012)
Purpose: The purpose of this project was to observe current warm-up practices in snowboard athletes and evaluate their physiological impact before competition. Methods: An observational design was used to monitor 4 athletes (2 female) at an Open National Snowboard Cross Championships. Activity patterns, core temperature, heart rate (HR), and time between warm-up and competition were measured. Athlete ratings of thermal comfort (TC) and thermal sensation (TS) were recorded before competition. Results: Significant barriers and challenges to an optimal warm-up included delays, environment, and logistics. Time gaps between structured warm-up and competition start time were in excess of 1 h (median = 68.8 min). Median average HR for 10 min (HR10) did not exceed 120 beats/min in the hour preceding competition, suggesting a suboptimal warmup intensity. Athletes rated their TC between comfortable and slightly uncomfortable and TS as neutral to slightly warm before the start of qualifications and finals. Conclusions: The observations of this project suggest significant gaps in current warm-up strategies used in snowboarding. These include inadequate general aerobic warm-up (based on intensity and duration), excessive time between warm-up and competition, and lack of a consistent and structured warm-up protocol. Future work is needed to evaluate the effectiveness of different warm-up strategies on muscle temperature and performance while determining the optimal length of time between warm-up and competition.